2018
DOI: 10.3389/fneur.2018.00826
|View full text |Cite
|
Sign up to set email alerts
|

Do Sensory Stimulation Programs Have an Impact on Consciousness Recovery?

Abstract: Objectives: Considering sensory stimulation programs (SSP) as a treatment for disorders of consciousness is still debated today. Previous studies investigating its efficacy were affected by various biases among which small sample size and spontaneous recovery. In this study, treatment-related changes were assessed using time-series design in patients with disorders of consciousness (i.e., vegetative state—VS and minimally conscious state—MCS).Methods: A withdrawal design (ABAB) was used. During B phases, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 53 publications
1
35
1
3
Order By: Relevance
“…Similar findings were reported by two groups using multimodal stimulation programmes [47,48]. The latter study showed that effects on the CRS-R, notably increased arousal and oromotor functions, were only found in MCS patients and not in VS patients [48].…”
Section: Which Medical Aspects Are Special In the Rehabilitation Osupporting
confidence: 86%
See 2 more Smart Citations
“…Similar findings were reported by two groups using multimodal stimulation programmes [47,48]. The latter study showed that effects on the CRS-R, notably increased arousal and oromotor functions, were only found in MCS patients and not in VS patients [48].…”
Section: Which Medical Aspects Are Special In the Rehabilitation Osupporting
confidence: 86%
“…In a preliminary report of a randomised placebo-controlled trial assessing the effect of familiar auditory sensory training, Pape and colleagues noted significant gains in the Coma-near-coma scale, representing arousal and awareness in patients with DOC [46]. Similar findings were reported by two groups using multimodal stimulation programmes [47,48]. The latter study showed that effects on the CRS-R, notably increased arousal and oromotor functions, were only found in MCS patients and not in VS patients [48].…”
Section: Which Medical Aspects Are Special In the Rehabilitation Omentioning
confidence: 73%
See 1 more Smart Citation
“…[68][69][70][71] A recent uncontrolled ABAB protocol tested the effects of a multi-sensory stimulation program including auditory, visual, tactile, olfactory, and gustatory stimuli (20 minutes per session applied 3 days per week for 4 weeks). 72 Higher CRS-R total scores were observed during the treatments periods (B) compared to baselines (A) in MCS but not in UWS patients groups. Double-blind RCTs need to further evaluate the possible superiority of a multi-sensory approach as compared to only one type of stimulation.…”
Section: Sensory Stimulation Programsmentioning
confidence: 93%
“…Further, it can be easily used as a bedside-assessment tool for DOC patients. However, several studies (Boly et al, 2007;Di et al, 2007;Sharon et al, 2013;Liang et al, 2014;Bodien et al, 2017;Cheng et al, 2018) have also used fMRI, which provides both high-resolution structural imaging as well as functional imaging, thus giving crucial information for diagnosis that could possibly never be ascertained by EEG (Giacino et al, 2014). The biggest issue with fMRI is that it is extremely sensitive to movement artifacts and therefore is difficult to record for these patients.…”
Section: Introductionmentioning
confidence: 99%